How Myth Became History : Texas Exceptionalism in the Borderlands - Dean, John Emory (Book collections on Project MUSE., 2016)
"The book explores how border subjects have been created and disputed in cultural narratives of the Texas-Mexico border, comparing and analyzing Mexican, Mexican American, and Anglo literary representations of the border"--Provided by publisher.